Evaluating the effect of a smartphone-based self-help intervention on the quality of life of patients with acute coronary syndrome - Faezeh Setoudeh; Zahra Molazem; Giti Setoodeh; Parvin Ghaemmaghami (BMC Cardiovascular Disorders)
Abstract Purpose Patients with acute coronary syndrome (ACS) face various challenges in the physical, psychological, social and functional domains of their lives, with adverse effects on their quality of life. The present study evaluated the effects of a smartphone-based self-help intervention on the quality of life of patients with ACS. Design A randomized controlled trial. Methods Sixty-four ACS patients were selected via convenience sampling and randomly assigned to one of the intervention or control groups (32 participants in each group). The participants in the intervention group received a smartphone-based self-help intervention in six sessions for three weeks. The smartphone-based self-help intervention involved six educational sessions delivered via WhatsApp, covering disease-related knowledge, emotional regulation, cognitive restructuring, sleep hygiene, resilience, and self-care practices. Patients accessed the material asynchronously and applied it to their daily routines. Data were collected before, immediately after, and three weeks after the intervention via a demographic questionnaire and the Ferrans and Powers Quality of Life Index (QLI). The collected data were analyzed in SPSS, version 22. Results There were no statistically significant differences between the two study groups regarding the quality-of-life mean scores measured before (p = 0.92) and immediately after (p = 0.26) the intervention. Three weeks after the intervention, however, the intervention group’s mean quality of life score was greater than that of the control group (p = 0.03). The results of the repeated-measures ANOVA revealed that the mean quality-of-life scores in the intervention group increased, whereas the mean quality-of-life scores in the control group remained stable. Conclusion The results of this study indicated that a smartphone-based self-help intervention effectively improved the quality of life of patients with ACS. Nurse managers and clinical nurses can utilize these findings to increase the quality of life of patients. Trial registration This trial was prospectively registered in the Iranian Registry of Clinical Trial (IRCT20220424054627N1) on 15 May 2022.